Correlation between fecal biomarkers and the presence of antineutrophil cytoplasmic antibodies with ulcerative colitis disease activity - Büşra Usta; Demet Gür Vural; Asuman Birinci; Müge Ustaoğlu Dede (Romanian Journal of Laboratory Medicine)
Although colonoscopy remains the gold standard for Ulcerative colitis (UC) diagnosis due to its invasive and costly nature, non-invasive biomarkers are gaining importance in disease activity monitoring and diagnosis. In our study, we aimed to evaluate the correlation of fecal calprotectin (FC) and fecal lactoferrin (FL) levels with the disease activity according to 3 different disease activity indices and to investigate the relationship between the presence of peri-nuclear anti-neutrophil antibody (p-ANCA) and disease activity.